The dual adjustment approach with an application to the consumption function - Mustafa Ismihan (Central Bank Review (CBR), 2019)
For theoretical and statistical reasons, it is important to decompose some series into dual components in order to understand their permanent and temporary movements as well as their dual co-movements. This study, therefore, aims to introduce the dual adjustment approach for the nonstationary macroeconomic variables. In line with this aim, the concept of common Hodrick-Prescott (HP) trend and a simple test for the existence of such relationship (Common HP trending) are also provided. The dual adjustment approach provides an alternative to the cointegration analysis for some cases, e.g., consumption function, by relaxing the implicit assumption of the singular adjustment in cointegration analysis. Our empirical results indicate that while personal consumption expenditure and disposable income are not cointegrated in the US over the period 1929–2017, these variables have a common HP trend. Additionally, it is shown that there is some evidence of dual adjustment in the behavior of US aggregate consumption.
Keywords: 330; Time series analysis; Dual co-movement; Common HP trend; Dual adjustment